THE INFLUENCE OF E-COMMERCE ADOPTION AMONG GENERATION Z DURING THE COVID-19 PANDEMIC - Zilaela Yasin; Genoveva Genoveva; Filda Rahmiati (Universitas Pelita Harapan, 2024)
At the beginning of 2020, Indonesia was fighting a virus that shocked the world, namely COVID-19. Every day the spread of the virus continues to increase. So that the government applies various ways so that the virus does not spread quickly, the ways the government is doing include social distancing, health protocols, working from home, and self-isolation. With a situation like this, some sectors are up for improvement such as online services, especially e-commerce. E-commerce is an online shopping platform that can meet our needs when we are not allowed to leave the house if there is nothing important. This study aims to obtain a significant variable regarding the acceptance of server-based e-commerce users in Indonesia, especially for Generation Z by adopting the UTAUT model and adding one mediating variable, namely Trust. This study uses quantitative research by distributing online questionnaires with 30 questions, taking a sample of 237 respondents, and using SmartPLS 3.3.3 (Partial Least Square-Structural Equation Model). The results of this study, that of the seven hypotheses proposed, two hypotheses were declared non-significant influence (performance expectancy to trust and performance expectancy to behavioural intention to use), while the other five hypotheses were stated positive significant influence and accepted.